Hepatitis of unknown etiology in children: What we know and what we can do? - Zhu, Mingyu; Chen, Li (Frontiers in Microbiology, 2022)
Recently, acute hepatitis of unknown etiology in children has gained great concern since March 2022. The disease was first reported by Public Health Scotland. Cases increased rapidly and are now reported in 33 countries worldwide. All cases are predominantly aged under 5 years old. Most patients present with jaundice, and remarkably, some cases progress to acute liver failure. Until now, the etiology is not fully elucidated, and the investigations are ongoing. Adenovirus infection seems to be an important factor. Several hypotheses on the etiology have been proposed. This review aims to summarize current research progress and put forward some suggestions.